Innovations in insuring the poor: Innovations in insuring the poor: Overview - Hill, Ruth Vargas; Torero, Máximo (International Food Policy Research Institute, 2009)
Risk characterizes life for many of the world’s poorest households. They are more likely to be located in environments where livelihoods are highly susceptible to weather and price variability and where health risks are pervasive. When these risks are uninsured, they not only reduce the current welfare of poor rural households, but also threaten future income growth and thus perpetuate poverty. Reducing the risks faced by poor households, and enabling poor households to better deal with bad events when they do occur, is essential to improving their welfare in the short run and their opportunities for income growth in the long run. This set of briefs considers how to increase the riskmanagement mechanisms available to poor households. The focus is how to develop insurance markets, along with other financial instruments such as credit and savings and ex post mechanisms such as social protection policies.